Modificación del ajuste de Ahnert para calcular periodos de retorno de precipitaciones extremas en ambientes de elevada variabilidad pluvial. Aplicación a la comunidad valenciana - De Luis, Martín; González-Hidalgo, José Carlos; Raventós, Josep; Sánchez, Juan Rafael (Geographicalia, 2016)
A new version of Ahnert model’s (1986) to calculate recurrence intervals of extreme events is presented, and the results are compared with Gumbel approach. The residual analysis of both function applied to 96 climatic stations in Comunidad Valenciana (E of Spain) suggest that in environments of extreme rainfall variability, as those under Mediterranean climate, the Ahnert modification approach can be more acute.